Integral recycling of municipal solid waste incineration (MSWI) bottom ash fines (0–2 mm) and industrial powder wastes by cold-bonding pelletization. (April 2017) - Tang, P.; Brouwers, H.J.H.
Highlights: Integrated recycle and reuse of several industrial solid wastes. Production of artificial lightweight cold bonded aggregates. Improvement of the produced lightweight aggregate properties. Mechanism description of the methods improving the aggregates properties. Leaching behaviour evaluation of the produced lightweight aggregates. Abstract: The cold-bonding pelletizing technique is applied in this study as an integrated method to recycle municipal solid waste incineration (MSWI) bottom ash fines (BAF, 0–2 mm) and several other industrial powder wastes. Artificial lightweight aggregates are produced successfully based on the combination of these solid wastes, and the properties of these artificial aggregates are investigated and then compared with others' results reported in literature. Additionally, methods for improving the aggregate properties are suggested, and the corresponding experimental results show that increasing the BAF amount, higher binder content and addition of polypropylene fibres can improve the pellet properties (bulk density, crushing resistance, etc.). The mechanisms regarding to the improvement of the pellet properties are discussed. Furthermore, the leaching behaviours of contaminants from the produced aggregates are investigated and compared with Dutch environmental legislation. The application of these produced artificial lightweight aggregates are proposed according to their properties.